A PHONOLOGICAL ANALYSIS ON MADURESE ENGLISH TEACHER’S PRONUNCIATION IN READING AN ENGLISH TEXT - Saputri, Tiyas (Department of English Language Education, UIN Sunan Ampel Surabaya, 2016)
This study concerns on a phonological analysis on Madurese English teacher?s pronunciation in reading an English text. The writer identified kinds of oscillographic pronunciation made by Madurese English teachers in reading an English text, the differences of oscillographic pronunciation between Madurese English teachers and that of the English native speaker in reading an English text and how Madurese language characteristics influences Madurese English teachers? pronunciation. In the process of data collection, she used descriptive qualitative. She observed and recorded the Madurese English teachers?pronunciation by using MP4 then analysed it by using Praat program version 4027. Then, she found that in reading the English text entitled „insomnia?, the oscillographic pronunciation of Subject 2 and Subject 3 when it is compared to subject 1 is different and makes different meaning, but for some words, it is slightly different but it does not make different meaning. Furthermore, it is found that Madurese language characteristics influence Subject 2 and Subject 3 in reading the English text. Therefore, in reading it, they made some sound changes: vowel, consonant and diphthong. The sound changes are: 1). the vowel changes: ???????;???, ???????;???, ???????, ???????;???;???, ???????;???;???, ???????, 2). the consonant changes: ???????, ????????, ???????, ???????, 3). the diphthong changes: ????????;???, ????????;???;???, ????????, ????????, ????????;???. In reading it, it is found that subject 2 and subject 3 also made deletion and addition. It is, thus, concluded that the pronunciation of subject 2 and subject 3 are unintelligible because they often mispronounce which can make their students do not understand their saying.